Impact of Financial Development on Economic Growth in Nigeria - Ayeni, Abigael Feranmi; Alexander, Anfofum A.; Alfa, Yakubu; Saheed, Zakaree S.; Ikubor, Jude (ABUAD Journal of Social and Management Sciences, 2024)
In Nigeria, financial development has been fluctuating and has not made significant impact on economic growth as a result of inadequate credit to the private sector that is supposed to improve investment in the economy. This study therefore examines the impact of financial development on economic growth in Nigeria, covering 1986 to 2022. The autoregressive distributed lag model was employed and the long run result reveals that interest rate (INT), lagged value of broad money supply (M2(-1)) and domestic credit to private sector (DCP) have positive impacts on GDPG while broad money supply (M2) has a negative impact on GDPG. The short run estimate indicates that INT and DCP have positive impact on economic growth, while the coefficient of M2 has negative impact on economic growth in Nigeria. In conclusion, financial development can be said to contribute to economic growth. This is because, when government allocates adequate credit to private sectors, investments are made in enhancing the productivity that will encourage investments to take place. These investments will lead to employment generation, and in turn lead to output growth. In this regard, the study recommends that the Nigerian government should increase allocation of credit to the private sector in order to improve investment and ensure the autonomy of relevant monetary authorities.